Penyelesaian Perkara Kecelakaan Lalu Lintas Melalui Pendekatan Restorative Justice Di Kota Pariaman - Atta Mananda; Widya Yoseva; Amanda Bherlyana Putri; Suci Nurjannah Yuansyah (Universitas Sumatera Barat, 2026)
Traffic accidents are a common legal event in society and can result in losses in the form of property damage, injuries, or even death. Traffic accident cases are generally resolved through the criminal justice process. However, developments in modern criminal law offer an alternative solution through a restorative justice approach, which emphasizes restoration of the situation, conflict resolution, and achieving justice for both victims and perpetrators. This study aims to determine the implementation of traffic accident case resolution through a restorative justice approach in Pariaman City, the factors influencing its implementation, and the effectiveness of this approach in achieving justice for all parties. The research method used is empirical legal research with a qualitative descriptive approach. Data were obtained through interviews with police officers, victims, and perpetrators, as well as through documentation studies related to traffic accident case resolution in Pariaman City. The data obtained were then analyzed qualitatively to provide an overview of the application of restorative justice in law enforcement practice. The results indicate that traffic accident case resolution through a restorative justice approach in Pariaman City is carried out by bringing together victims and perpetrators to reach a peaceful agreement through deliberation. The application of this approach offers benefits in the form of restitution for victims' losses, the creation of peace between the parties, and faster and more efficient case resolution compared to the criminal justice process. However, its implementation still faces several obstacles, such as a lack of public understanding of the concept of restorative justice, conflicting interests between victims and perpetrators, and limitations in mediation. Therefore, increased outreach, strengthening the role of law enforcement officials, and effective oversight are needed to ensure optimal implementation of restorative justice.